A family of NADPH/NADP+ biosensors reveals in vivo dynamics of central redox metabolism across eukaryotes - Scherschel, Marie; Niemeier, Jan-Ole; Jacobs, Lianne J. H. C.; Hoffmann, Markus D. A.; Diederich, Anika; Bell, Christopher; Höhne, Pascal; Raetz, Sonja; Kroll, Johanna B.; Steinbeck, Janina; Lichtenauer, Sophie; Multhoff, Jan; et al. (Nature communications, 2024)
The NADPH/NADP + redox couple is central to metabolism and redox signalling. NADP redox state is differentially regulated by distinct enzymatic machineries at the subcellular compartment level. Nonetheless, a detailed understanding of subcellular NADP redox dynamics is limited by the availability of appropriate tools. Here, we introduce NAPstars, a family of genetically encoded, fluorescent protein-based NADP redox state biosensors. NAPstars offer real-time, specific measurements, across a broad-range of NADP redox states, with subcellular resolution. NAPstar measurements in yeast, plants, and mammalian cell models, reveal a conserved robustness of cytosolic NADP redox homoeostasis. NAPstars uncover cell cycle-linked NADP redox oscillations in yeast and illumination- and hypoxia-dependent NADP redox changes in plant leaves. By applying NAPstars in combination with selective impairment of the glutathione and thioredoxin antioxidative pathways under acute oxidative challenge, we find an unexpected and conserved role for the glutathione system as the primary mediator of antioxidative electron flux. This article presents NAPstars, a family of genetically-encoded biosensors that enable real-time monitoring of NADP redox dynamics across species. The sensors reveal robust NADP redox regulation, cell-cycle-linked NADP oscillations, and glutathione as the major conduit for anti-oxidative electron flux.